College english and communication - Camp, Sue C. (Glencoe/McGraw-Hill, 2002)
College English and Communication, eighth edition continues to provide up-to-date coverage of key topics such as cultural diversity, ethics, global communications, electronic communications, and using the Internet for communication and online resources. The text covers the basics of grammar, spelling, and punctuation while incorporating customer service, business correspondence, the job search process, oral communication, and technology.